2014
DOI: 10.1016/j.biopsych.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

MAOA Genotype, Childhood Maltreatment, and Their Interaction in the Etiology of Adult Antisocial Behaviors

Abstract: Background Maltreatment by an adult or caregiver during childhood is a prevalent and important predictor of antisocial behaviors in adulthood. A functional promoter polymorphism in the monoamine oxidase A (MAOA) gene has been implicated as a moderating factor in the relationship between childhood maltreatment and antisocial behaviors. Although there have been numerous attempts at replicating this observation, results remain inconclusive. Methods We examined this gene-environment interaction hypothesis in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…As a matter of fact, most of the studies on the genetic association with antisocial behavior reached statistical significance in groups of individuals who had been subjected to child abuse and maltreatment, low parenting, maternal distress, and/or low socio-economic status. 13,78,[125][126][127]140 On the other hand, previous G Â E association studies demonstrating that single gene variants in combination with the adverse environment are associated to aggression and conduct disorders, like the groundbreaking work of Caspi and colleagues on MAOA uVNTR, 7 failed to be replicated in larger samples of individuals by very recent publications, 49,50 raising again some doubts about such an association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, most of the studies on the genetic association with antisocial behavior reached statistical significance in groups of individuals who had been subjected to child abuse and maltreatment, low parenting, maternal distress, and/or low socio-economic status. 13,78,[125][126][127]140 On the other hand, previous G Â E association studies demonstrating that single gene variants in combination with the adverse environment are associated to aggression and conduct disorders, like the groundbreaking work of Caspi and colleagues on MAOA uVNTR, 7 failed to be replicated in larger samples of individuals by very recent publications, 49,50 raising again some doubts about such an association.…”
Section: Discussionmentioning
confidence: 99%
“…28 A number of subsequent studies confirmed these results, 29,31,[37][38][39][40][41][42][43][44][45] while others failed to replicate them. [46][47][48][49][50] Among these papers, two meta-analyses, published in 2006 and 2007, strongly supported the original hypothesis, 40,41 while two very recent studies published in 2013 and conducted in very large samples did not replicate these previous findings. In detail, as part of the Pelotas 1993 Birth Cohort Study, Kieling and colleagues tested 1998 adolescent males from low-and middle-income countries for the interaction between MAOA uVNTR genotype and childhood maltreatment in the occurrence of ''externalizing behavior,'' that is a behavior which comprises most antisocial traits including aggression, and represents a major risk factor for later juvenile delinquency, adult crime, and violence.…”
Section: Introductionmentioning
confidence: 88%
“…The most recent meta-analysis reported that early adversity predicted antisocial outcomes more strongly for low, relative to high, activity MAOA genotype (p = .0044), with the interaction being particularly pronounced for maltreatment (p = .0000008). However, the findings could not be confirmed in all samples (e.g., Kieling et al 2013;Haberstick et al 2014), leaving room for ambiguity. In female subjects, findings suggested differential interaction patterns.…”
Section: Introductionmentioning
confidence: 85%
“…10 However, the largest study on this issue, with more than 4000 individuals, could not confirm the hypothesis that this MAOA genotype moderates the relationship between childhood maltreatment and antisocial behavior, but found statistically non-significant evidence for a main effect of MAOA genotype on having disposition toward violence. 11 Thus, the issue of a ‘warrior gene’ has remained controversial.…”
Section: Introductionmentioning
confidence: 99%